Systematic Review and Meta-Analysis of Endurance Exercise Training Protocols for Mice - Massett, Michael P.; Matejka, Caitlyn; Kim, Hyoseon (Frontiers in Physiology, 2021)
Inbred and genetically modified mice are frequently used to investigate the molecular mechanisms responsible for the beneficial adaptations to exercise training. However, published paradigms for exercise training in mice are variable, making comparisons across studies for training efficacy difficult. The purpose of this systematic review and meta-analysis was to characterize the diversity across published treadmill-based endurance exercise training protocols for mice and to identify training protocol parameters that moderate the adaptations to endurance exercise training in mice. Published studies were retrieved from PubMed and EMBASE and reviewed for the following inclusion criteria: inbred mice; inclusion of a sedentary group; and exercise training using a motorized treadmill. Fifty-eight articles met those inclusion criteria and also included a “classical” marker of training efficacy. Outcome measures included changes in exercise performance, V ̇O2max, skeletal muscle oxidative enzyme activity, blood lactate levels, or exercise-induced cardiac hypertrophy. The majority of studies were conducted using male mice. Approximately 48% of studies included all information regarding exercise training protocol parameters. Meta-analysis was performed using 105 distinct training groups (i.e., EX-SED pairs). Exercise training had a significant effect on training outcomes, but with high heterogeneity (Hedges’ g = 1.70, 95% CI = 1.47-1.94, Tau2 = 1.14, I2 = 80.4%, prediction interval = -0.43-3.84). Heterogeneity was partially explained by subgroup differences in treadmill incline, training duration, exercise performance test type, and outcome variable. Subsequent analyses were performed on subsets of studies based on training outcome, exercise performance or biochemical markers. Exercise training significantly improved performance outcomes (Hedges’ g = 1.85, 95% CI = 1.55-2.15). Subgroup differences were observed for treadmill incline, training duration, and exercise performance test protocol on improvements in performance. Biochemical markers also changed significantly with training (Hedges’ g = 1.62, 95% CI = 1.14-2.11). Subgroup differences were observed for strain, sex, exercise session time, and training duration. These results demonstrate there is a high degree of heterogeneity across exercise training studies in mice. Training duration had the most significant impact on training outcome. However, the magnitude of the effect of exercise training varies based on the marker used to assess training efficacy.